Penguatan Kelembagaan Kelompok Sadar Wisata Desa Wisata Keliki Kecamatan Tegallalang Kabupaten Gianyar - Kalpikawati, Ida Ayu; Pinaria, Chintia; Sudiksa, I Nyoman (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
Keliki Village has been designated as a tourist village in 2020. As a relatively new tourist village, Keliki Tourism Village already has a tourism awareness group (Pokdarwis), but the tourism programme developed to optimise the village's potential has not been plemented. There are no documented activities in the tourism sector, even though in reality there are already several tourism businesses in Keliki Village, but they are still managed personally. This community service activity aims to provide institutional strengthening through increasing and developing the competence of Pokdarwis members in managing the Keliki Tourism Village. This service is carried out through the initial assessment stage, programme preparation, and service activities that involve the active participation of Pokdarwis members and the tourism community to formulate needs analyses and identify village potential. The number of service participants was 15, consisting of Pokdarwis members, the general public, and tourism actors in Keliki Village. The form of activity is socialisation, and the implementation date is June 15–16, 2023. The evaluation of this activity is carried out by distributing questionnaires to the participants. The results of the respondent's assessment obtained an average score of 3.80 with very good criteria, which means that the participants felt very satisfied with the activities carried out, and the participants strongly agreed that this activity could be continued again because they considered this activity to be very useful in helping Pokdarwis members develop tourism at Keliki Tourism Village.